2022
DOI: 10.1177/15270025221123315
|View full text |Cite
|
Sign up to set email alerts
|

The Value of College Athletics in the Labor Market: Results from a Resume Audit Field Experiment

Abstract: Employers may favor applicants who played college sports if athletics participation contributes to leadership, conscientiousness, discipline, and other traits that are desirable for labor-market productivity. We conduct a resume audit to estimate the causal effect of listing collegiate athletics on employer callbacks and test for subgroup effects by ethnicity, gender, and sport type. We applied to more than 450 jobs on a large, well-known job board. For each job listing, we submitted two fictitious resumes, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…This study complemented two earlier audit studies on the effects of physical exercise on employment chances. While our insignificant average point estimate of 1.0 pp is higher than the insignificant estimate of Paul et al (2023) (-1.5 pp), it is below the significant estimate of Rooth (2011) (+1.9 pp). Moreover, it is also below the estimated effect of graduating with honors or engaging in the board of a student organization (+1.6 pp for each activity), as found in a similar Flemish experiment (Baert and Verhaest, 2021).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…This study complemented two earlier audit studies on the effects of physical exercise on employment chances. While our insignificant average point estimate of 1.0 pp is higher than the insignificant estimate of Paul et al (2023) (-1.5 pp), it is below the significant estimate of Rooth (2011) (+1.9 pp). Moreover, it is also below the estimated effect of graduating with honors or engaging in the board of a student organization (+1.6 pp for each activity), as found in a similar Flemish experiment (Baert and Verhaest, 2021).…”
Section: Discussioncontrasting
confidence: 85%
“…However, the adopted exclusion restrictions in some of these studies may be open to debate. As an alternative, Rooth (2011) and Paul et al (2023) have therefore relied on experiments in which fictitious resumes were sent to real vacancies. Also their results are mixed as the former study found a small but meaningful effect of sport participation among Swedish college graduates while the latter did not detect any effect for US graduates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation